Pemberian Makanan Tambahan Dan Psikoedukasi Pola Asuh Metode (Cium,Peluk Dan Beri Asupan) Cilukba Untuk Meningkatkan Pengetahuan Orang Tua Mengenai Stunting di Kelurahan Oesapa Selatan, Kecamatan Kelapa Lima, Kota Kupang - Maria Fatima Saga Wea; Fitri Handayani; Johana Art Cindy Peny (Lembaga Pengembangan Kinerja Dosen, 2024)
Stunting is a nutritional problem caused by insufficient nutritional intake for a long time. The condition of failure to thrive in children under five is a result of chronic malnutrition so that the child is too short for his age. Indonesia is among the highest in stunting cases with a prevalence of 37.2% compared to other neighboring countries. Indonesia targets the stunting rate to fall to 14% in 2024, while the stunting rate in 2021 will reach 24%. The impact of stunting is an increase in morbidity and mortality rates in children, growth in body posture or height that is not optimal compared to the child's age, disruption of motor development, increasing the incidence of degenerative diseases, less than optimal learning performance so that children's cognitive and productivity are affected and that furthermore is the increase in Health costs. The Kupang City Government, in an effort to reduce the prevalence rate of stunting below 10% in 2024, is carrying out convergence work or cross-sectoral collaboration within the scope of Pentahelix (Government, PT, Private, Community and Mass Media). The foster parent program is a form of care and effort made by involving all sectors in accelerating the prevention and handling of stunting in toddlers. The sub-districts that are used as places for community service activities are Penfui and Oesapa Selatan Subdistricts, Kupang City. The foster parent program aims to help families who really need health care for children suffering from stunting and malnutrition, and this is based on a sense of care and responsibility. The Kupang Ministry of Health Polytechnic, as one of the implementations of health transformation, supports the government's program in strengthening primary health services, especially stunting, and is expected to be involved and become a team in accelerating the prevention and handling of stunting in Kupang City. The method for implementing this community activity is the Peekaboo Psychoeducational method, namely the Kiss, Hug and Give Feed method as well as providing nutritious food to children aged 6-24 months for 90 days. The results of this community service are the achievement of measurement data on children's body weight, improvements in nutritional value/body weight of children suffering from stunting and increased knowledge of the psychoeducational parenting style of the Peekaboo method to increase parents' knowledge about stunting.